An end to medieval reindeer in Scotland - Clutton-Brock, Juliet; MacGregor, Arthur (Proceedings of the Society of Antiquaries of Scotland, 1989)
This review of the present evidence concludes that endemic, wild reindeer became extinct in Britain c 8000 years ago. Au